Exploring the genetic diversity of Edwardsiella ictaluri in Vietnamese striped catfish (Pangasianodon hypophthalmus) farms over a 20-year period - Payne, Christopher J.; Grace, Kathryn; Phuong, Vo Hong; Phuoc, Nguyen Ngoc; Dung, Tu Thanh; Phuoc, Le Hong; Crumlish, Margaret (Frontiers in Marine Science, 2023)
Since first being identified in 1999, disease outbreaks from Edwardsiella ictaluri remain a significant health challenge for the farmed catfish sector in Vietnam. To better understand the population structure of E. ictaluri circulating in Vietnamese striped catfish (Pangasianodon hypophthalmus) farms, this study aimed to investigate the genetic diversity of 83 E. ictaluri isolates recovered from natural disease outbreaks occurring in the Mekong Delta region between 2001 and 2021. Pulsed-field gel electrophoresis resolved isolates into 15 pulsotypes following restriction digest with speI, with a Simpson’s diversity index of 0.8548. The genetic fingerprints of isolates recovered from recent outbreaks across different provinces were highly shared (100% similarity), suggesting clonal expansion within the production systems situated in the Mekong Delta region. Findings from this study also showed that E. ictaluri populations circulating this region have changed over time, as isolates recovered between 2001 and 2011 were genetically distinct from those recovered after 2017. Furthermore, isolates recovered after 2004 and 2010 lacked the virulence gene traD and a 5.8 Kb plasmid DNA fragment, respectively. Findings from this study illustrate the need for continued epidemiological monitoring of E. ictaluri to ensure prevention and treatment strategies in the Vietnamese striped catfish sector remain robust and effective.